Respuesta :
1)
g(x) = f(x)+12 represents translating f(x) 12 units up to get g(x). This is because y = f(x), so we're effectively adding 12 to each y coordinate of the points on f(x) to have them move to the points on g(x).
note: the term "translating" is another way of saying "shifting" or "sliding".
===================================================
2)
h(x) = f(x)-7 means translating f(x) 7 units down to get h(x). We use the same reasoning as in problem 1. The general form is h(x) = f(x)+k, and in this case, k = -7. The negative k value tells us to shift down.
===================================================
3)
g(x) = f(x+8) means we translate 8 units to the left. The general template is g(x) = f(x-h). If h > 0, then we shift right. If h < 0, then we shift left. The amount that is shifted is equal to the absolute value of h.
===================================================
4)
h(x) = f(x-14) tells us to shift f(x) 14 units to the right. Same idea as problem 3, but now h = 14.
===================================================
5)
g(x) = 4*f(x) means we vertically stretch f(x) by a factor of 4. Since y = f(x), we are effectively doing g(x) = 4*f(x) = 4*y, which pulls the y coordinates upward by a factor of 4. A point like (1,2) will jump to (1,8) after multiplying the y coordinate by 4.
===================================================
6)
g(x) = f(5x) tells us to horizontally compress f(x) by a factor of 5. The general template is g(x) = f(a*x) where the 'a' determines horizontal stretching or compression. If [tex]0 \le a \le 1[/tex], then we have horizontal stretching going on. If [tex]a > 1[/tex], then we'll have horizontal compression.
Function transformation involves changing the form of a function
The function is given as:
[tex]\mathbf{f(x) = 3x + 5}[/tex]
1. g(x) = f(x) + 12
This gives
[tex]\mathbf{g(x) = 3x + 5 + 12}[/tex]
[tex]\mathbf{g(x) = 3x + 17}[/tex]
g(x) = f(x) + 12 relates to f(x) by shifting f(x) 12 units up
2. h(x) = f(x) - 7
This gives
[tex]\mathbf{h(x) = 3x + 5 - 7}[/tex]
[tex]\mathbf{h(x) = 3x - 2}[/tex]
h(x) = f(x) - 7 relates to f(x) by shifting f(x) 7 units down
3. g(x) = f(x + 8)
This gives
[tex]\mathbf{g(x) = 3(x + 8) + 5}[/tex]
[tex]\mathbf{g(x) = 3x + 24 + 5}[/tex]
[tex]\mathbf{g(x) = 3x +29}[/tex]
g(x) = f(x + 8) relates to f(x) by shifting f(x) 8 units left
4. h(x) = f(x - 14)
This gives
[tex]\mathbf{h(x) = 3(x - 14) + 5}[/tex]
[tex]\mathbf{h(x) = 3x - 42 + 5}[/tex]
[tex]\mathbf{h(x) = 3x -37}[/tex]
h(x) = f(x - 14) relates to f(x) by shifting f(x) 14 units right
5. g(x) = 4f(x)
This gives
[tex]\mathbf{g(x) = 4(3x + 5)}[/tex]
[tex]\mathbf{g(x) = 12x + 20}[/tex]
g(x) = 4f(x) relates to f(x) by vertically stretching f(x) by a factor of 4
6. h(x) = f(5x)
This gives
[tex]\mathbf{h(x) = 3(5x) + 5}[/tex]
[tex]\mathbf{h(x) = 15x + 5}[/tex]
h(x) = f(5x) relates to f(x) by horizontally stretching f(x) by a factor of 5
Read more about function transformations at:
https://brainly.com/question/13810353